Análise comparativa de sistemas fotovoltaicos conectados a rede instalados em Curitiba com diferentes topologias - Silva, Joel Claudiano da (2022)
The water crisis aggravated in 2020 evidenced the dependence of the National Interconnected System on highcost energy generation sources to supply the demand for electricity in periods of water scarcity. The main factors for the increase in electricity costs were the dispatch of Generation by Thermoelectric Power Plants and the importation of Electric Energy from Argentina and Uruguay, according to the Electric Energy Commercialization Chamber. This scenario promoted an exponential growth of the portion of the Brazilian energy matrix composed of Photovoltaic Generation, both for the emergence of Solar farms, as well as commercial or residential systems. This work presents a comparative analysis between Photovoltaic Systems Connected to the Network installed in the city of Curitiba, in different locations, with different topologies, with inverters and modules of different characteristics, with different orientations and inclinations, according to the availability of roof areas in each location. The initial projections of annual generation were analyzed and the result obtained was verified, seeking the improvement of the technique used by designers and integrators of photovoltaic systems, to obtain a more assertive estimate possible, aiming at obtaining the best result for technical and economic feasibility. The Merit Indices: Capacity Factor, Productivity and Performance Rate of seven photovoltaic systems installed in the city of Curitiba were analyzed, with the objective of proving the studies already carried out on the potential of power generation in Curitiba, from the analysis of the data of electricity generation of these systems and the irradiation data obtained from the National Institute of Meteorology. The choice of inverter and the installation mode of photovoltaic panels are determining factors to maximize the performance of the photovoltaic system.